Isoflavones and probiotics effect on bone calcium and bone cells in rats - Iskandar Azmy Harahap; Maciej Kuligowski; Marcin Schmidt; Paweł Kurzawa; Ewa Pruszyńska-Oszmałek; Maciej Sassek; Joanna Suliburska (Heliyon, 2023)
Isoflavones and probiotics have shown the therapeutic potential to alter calcium absorption and bone cell metabolism. This study sought to ascertain the effect of isoflavones and probiotics on calcium status and bone health in healthy female rats. Forty-eight adult female Wistar rats were grouped and fed: a standard diet (control); and standard diets with tempeh; soy; daidzein and genistein; Lactobacillus acidophilus; and a combination of daidzein, genistein, and L. acidophilus. The biochemical serum parameters, such as alanine transaminase, aspartate transaminase, glucose, and triacylglycerol concentrations, were measured, and calcium contents in tissues were determined. After staining the bone with hematoxylin and eosin, the number of osteoblasts, osteocytes, and the percentage of bone marrow adipocytes were counted. Compared with the control group, the soy group showed a significantly lower triacylglycerol concentration. The L. acidophilus group considerably increased the calcium content in the femoral bone. The daidzein and genistein, L. acidophilus, and a combination of daidzein, genistein, and L. acidophilus groups showed significantly lower calcium contents in the heart and kidneys. The daidzein and genistein group significantly enhanced the number of osteoblasts and osteocytes. A substantial inverse correlation was observed between calcium contents in kidneys and osteoblasts. In conclusion, the combination of daidzein, genistein, and L. acidophilus may improve bone calcium concentrations and bone cells. However, no synergistic effect between isoflavones and probiotics was detected in this study.